2011
DOI: 10.1177/0907568210373668
|View full text |Cite
|
Sign up to set email alerts
|

No logo? Children’s consumption of fashion

Abstract: In this article data are presented on children's appraisal of clothing retailers and brands, and how this interacts with their identity and social contexts. In exploration of some of the meanings and processes surrounding children's consumption of branded or labelled clothing, two case studies of child consumers are profiled: one who actively consumed designer-label clothing, and another for whom it held limited significance. It is argued that children aged 12 and under knowingly and skilfully use their consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
9

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 23 publications
(18 reference statements)
1
17
0
9
Order By: Relevance
“…The overwhelmingly middle-class intake of the school suggests that social class was not a factor, though habitus may have been (Sedano, 2012): the 'cool girls' were notable in their comparatively high interest in brand-name and designer clothing, and some had highlights in their hair (Pilcher, 2011), whereas the central trio in the 'normal people' group were high achievers. It is also the case that, in a setting in which ethnicity was played down so much that it was almost invisible, two of the 'nice girls' group and one of the intermediate-status best-friend pair were of ethnic minority origin (Melissa and Britney Turkish, Athena Chinese).…”
Section: Data Source and Methodsmentioning
confidence: 99%
“…The overwhelmingly middle-class intake of the school suggests that social class was not a factor, though habitus may have been (Sedano, 2012): the 'cool girls' were notable in their comparatively high interest in brand-name and designer clothing, and some had highlights in their hair (Pilcher, 2011), whereas the central trio in the 'normal people' group were high achievers. It is also the case that, in a setting in which ethnicity was played down so much that it was almost invisible, two of the 'nice girls' group and one of the intermediate-status best-friend pair were of ethnic minority origin (Melissa and Britney Turkish, Athena Chinese).…”
Section: Data Source and Methodsmentioning
confidence: 99%
“…The relationship between equality discourse and economic inequality is discussed by Fernqvist (2013) based on the Swedish school. She points to clothes as one of the areas where poverty is visible (Gordon, Holland, Lahelma, & Campling, 2000), while previous research has shown the symbolic value of clothes as a vital part of self-presentation among children (König, 2008;Pilcher, 2011;Ridge, 2002). An important point made by Fernqvist is that the children are given the responsibility to conceal their poverty, because equality is given such high ideological meaning.…”
Section: Discussionmentioning
confidence: 99%
“…The need to express identity and community was apparent in many drawings by the older children, especially the ones concerning clothes (cf. Pilcher, 2011;Tufte, 2007). Instrumental use was connected to mobile phones and computers.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Children around the age of twelve often use their consumer knowledge to creatively and skilfully construct their unique identity and to fit into their peer groups (Pilcher, 2011;Waerdahl, 2003), which has been described as the symbolic paradox of consumption (Simmel, trans. 1964;Tufte, 2007).…”
Section: Theory and Research Into Children As Consumersmentioning
confidence: 99%